2019
DOI: 10.1021/acs.cgd.9b00133
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Control by Pulsed Laser in Chemical Deposition Illustrated in ZnO Crystal Growth

Abstract: The control of pulsed-laser-induced deposition was studied with the case of ZnO crystallization in a hydrothermal reaction. Crystal orientation, morphologies, and growth rate were observed to vary under different pulsed-laser irradiation conditions. Different energy barriers during nucleation and crystal growth processes were determined by stepped changes of input energy levels of a pulsed laser with the corresponding observations of the states of the material. Therefore, by precisely adjusting the pulsed-lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…The addition of acidic polymers could offer the control on crystal growth; for nucleation control, previous methods to control nucleation include usual cooling, evaporate crystallization, ultrasound, , and the application of electric field and magnetic field. One particular nucleation method called laser-induced nucleation (LIN) is the most documented technique, which could highly control nucleation sites by precisely adjusting the pulsed laser energy; morphological control could be obtained by LIN through adjusting the laser power density to selectively overcome the energy barriers of different surfaces of crystals. These benefits are observed in the work of ZnO morphology control by adjusting the pulsed laser energy to differentiate the growth rate on a Si(100) surface, as reported by S. Liu and C. R. Liu . With respect to the continuous-wave laser light, the polymorph of a glycine crystal could be selectively controlled by tuning laser polarization and power, according the account of Sugiyama and their co-workers .…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The addition of acidic polymers could offer the control on crystal growth; for nucleation control, previous methods to control nucleation include usual cooling, evaporate crystallization, ultrasound, , and the application of electric field and magnetic field. One particular nucleation method called laser-induced nucleation (LIN) is the most documented technique, which could highly control nucleation sites by precisely adjusting the pulsed laser energy; morphological control could be obtained by LIN through adjusting the laser power density to selectively overcome the energy barriers of different surfaces of crystals. These benefits are observed in the work of ZnO morphology control by adjusting the pulsed laser energy to differentiate the growth rate on a Si(100) surface, as reported by S. Liu and C. R. Liu . With respect to the continuous-wave laser light, the polymorph of a glycine crystal could be selectively controlled by tuning laser polarization and power, according the account of Sugiyama and their co-workers .…”
Section: Introductionmentioning
confidence: 84%
“…These benefits are observed in the work of ZnO morphology control by adjusting the pulsed laser energy to differentiate the growth rate on a Si(100) surface, as reported by S. Liu and C. R. Liu. 30 With respect to the continuous-wave laser light, the polymorph of a glycine crystal could be selectively controlled by tuning laser polarization and power, according the account of Sugiyama and their coworkers. 31 More recently, Cheng et al applied optical trapping with a focused continuous-wave near-infrared laser to demonstrate the morphology evolution of KCl crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Interesting reaction pathways were proposed by Liu and Liu by employing the pulsed-laser deposition technique to obtain a given morphology of ZnO [ 81 ]. The authors demonstrated that laser-induced crystal growth is a practical tool to tune the morphology of nanomaterials in a precise and effective manner.…”
Section: Resultsmentioning
confidence: 99%
“…ZnO crystals or intermediate species in this study were produced by the pulsed laser method, similar to the previous studies. 13 The precursor solution for producing ZnO crystals was prepared from zinc acetate dihydrate in alcoholic solution under basic conditions. 15 stirring at room temperature.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…Zinc oxide (ZnO) is one of the most common oxides that could be easily produced by hydrothermal reaction. In this work, ZnO as a vehicle for the study of crystallization was produced by the pulsed laser method. The pulsed laser as a new tool to study the crystallization , could “freeze” the crystallization process in a stepwise manner. For example, the nucleation could be initiated by a single laser pulse, and the following aging processes, such as recrystallization or dissolution–reprecipitation, could be inhibited after the single pulse .…”
Section: Introductionmentioning
confidence: 99%